2018
DOI: 10.1088/1751-8121/aaa92b
|View full text |Cite
|
Sign up to set email alerts
|

The bilinear–biquadratic model on the complete graph

Abstract: We study the spin-1 bilinear-biquadratic model on the complete graph of N sites, i.e., when each spin is interacting with every other spin with the same strength.Because of its complete permutation invariance, this Hamiltonian can be rewritten as the linear combination of the quadratic Casimir operators of su(3) and su(2).Using group representation theory, we explicitly diagonalize the Hamiltonian and map out the ground-state phase diagram of the model. Furthermore, the complete energy spectrum, with degenerac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Surprisingly, the precision bound is the same for any such state. PI singlet states are very relevant for experiments, since they have been experimentally created in cold gases [79,80] while they also appear in condensed matter physics [81].…”
Section: Singlet Statesmentioning
confidence: 99%
“…Surprisingly, the precision bound is the same for any such state. PI singlet states are very relevant for experiments, since they have been experimentally created in cold gases [79,80] while they also appear in condensed matter physics [81].…”
Section: Singlet Statesmentioning
confidence: 99%
“…Another interesting generalization that does not involve the spatial redistribution of the couplings would be to study less symmetric interactions; a natural candidate would be reducing the SU(3) symmetry to SU(2). In the case of spin-1 this is described by the bilinear-biquadratic interaction, which has already been studied on complete graphs [33]. Symmetric collective spin states have been studied, due to their experimental feasibility, also from a quantum metrology point of view [43,44], it would be interesting to study also bipartite models especially in the light of the experiment reported in [45].…”
Section: Discussionmentioning
confidence: 99%
“…( 6) will be proportional to the quadratic Casimir operator of the global SU (3) spin operators, and hence its eigenproblem simplifies to determining how the entire Hilbert space decomposes into SU(3) irreducible representations (irreps). This was discussed in [32] and also in [33] as a special case of the bilinearbiquadratic model on the complete graph.…”
Section: The Model Hamiltonianmentioning
confidence: 99%
“…where 𝑆 i denotes the spin-1 operator at lattice site i, and α = tan φ is the control parameter. The model has been investigated extensively using analytical and numerical methods, [8][9][10][11][12][13][14][15][16][17][18][19][20] exhibiting rich physics. Its ground state phase diagram has been mostly understood.…”
Section: Introductionmentioning
confidence: 99%